The association between peripheral blood inflammatory markers and anti-VEGF treatment response in patients with type 2 diabetic macular edema - Gu, Wenting; Wang, Min; Li, Zhizhe; Xu, Tianqi (Frontiers in Medicine, 2025)
AimThis study aimed to investigate the correlation between serum inflammatory markers of patients with diabetic macular edema (DME) and the efficacy of intravitreal anti-vascular endothelial growth factor (VEGF).MethodsThis was a single-center, prospective cohort study. Peripheral blood cell analysis was performed on 40 patients with confirmed type 2 diabetes complicated by DME, 40 healthy individuals, and 40 patients with confirmed type 2 diabetes without diabetic retinopathy. Neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), monocyte-to-lymphocyte ratio (MLR), and systemic immune-inflammation index [SII; (neutrophil count × platelet count)/lymphocyte count] were calculated. All patients with DME received three monthly intravitreal injections of anti-VEGF agents (ranibizumab). Correlation analyzes and linear regression models were used to investigate the relationships between systemic inflammatory markers and best-corrected visual acuity (BCVA) and central macular thickness (CMT) before and after anti-VEGF treatment in DME patients.ResultsThe NLR, PLR, and SII values in the DME group differed significantly from those in both the healthy and non-diabetic retinopathy (NDR) groups. Significant differences in MLR values were observed between the healthy and NDR groups. After a 3-month follow-up (following three injections), BCVA and CMT showed significant improvement before and after anti-VEGF treatment in DME patients. However, there were no significant differences in NLR, PLR, and SII before and after anti-VEGF treatment. MLR was significantly different before and after treatment. BCVA in the DME group before anti-VEGF treatment was positively correlated with NLR, PLR, and SII. CMT before anti-VEGF treatment was positively correlated with NLR, PLR, MLR, and SII. NLR, PLR, MLR, and SII were significantly correlated with BCVA and CMT. In multivariate linear regression analysis, only NLR was significantly correlated with CMT.ConclusionThe efficacy of anti-VEGF in DME is correlated with serum inflammatory markers. Additionally, NLR, PLR, MLR, and SII may serve as potential markers for DME treatment decisions. The finding that NLR remained significant in the multivariate analysis highlights its potential value as a simple, accessible prognostic biomarker for stratifying patients who may respond suboptimally to anti-VEGF treatment.